Pengembangan Media Gambar Untuk Penyuluhan Agama Kristen Bagi Anak Usia Dini di PAUD KB ANANDA Kecamatan Sipoholon Kabupaten Tapanuli Utara - Winda Manalu; Goklas J Manalu; Regina B.M Nainggolan; Damayanti Nababan; Melina Agustina Sipahutar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop image media as a tool for Christian religious education that can be applied to early childhood education activities. This study uses a research and development (R&D) method by implementing ADDIE which is limited to three stages due to time and material limitations. The data collection technique uses a questionnaire that is evaluated by media experts, linguists, and early childhood experts. Aspects of assessment by linguists include the suitability of the language to the child's age, clarity of language, readability and fluency, as well as the appropriateness of spelling and punctuation. The assessment results showed an average feasibility with a percentage reaching 93.25% and the category